High-performance thin-layer chromatography fingerprinting and anti-inflammatory and antinociceptive activities of Pyracantha coccinea M.Roem.: A laboratory-based study - Taheri, Yasaman; Naderi, Nima; Ayatollahi, Seyed Abdulmajid; Baghalpour, Navid; Mahroo-Bakhtiyari, Javad; Sharifi-Rad, Javad (Cellular and Molecular Biology, 2021)
This study aimed to investigate the high-performance thin-layer chromatography (HPTLC) fingerprinting and in-vivo anti-inflammatory and antinociceptive activities of different leaf extracts (ethanolic extract, n-hexane, chloroform, and ethyl acetate) of Pyracantha coccinea M.Roem. plant. A total of one hundred and twenty-four Wistar rats for anti-inflammatory and antinociceptive tests (carrageenan and formalin tests, respectively) were treated with two doses of the ethanolic extract (100 and 300 mg/kg), two doses of other plant fractions (30 and 100 mg/kg), Diclofenac (25 mg/kg) as the positive control, and normal saline as the negative control group, by oral gavage route. HPTLC fingerprinting is used for assay of terpenoids, flavonoids, alkaloids, and antioxidant activity. Treatment of the animal with the ethanolic extract at doses of 100 and 300 mg/kg, both ethyl acetate and chloroform fractions at the dose of 30 mg/kg and 100 mg/kg decreased the pain score in the formalin test and paw edema caused by carrageenan relative to control group significantly. Moreover, these extracts reported the highest amounts of flavonoid contents. In conclusion, phytochemicals present in Pyracantha coccinea M.Roem. leaves have anti-inflammatory and antinociceptive activities. Future studies are needed to identify the compounds with the anti-inflammatory and antinociceptive potential present in the plant.